Can posterior pericardiotomy reduce the incidence of postoperative atrial fibrillation after coronary artery bypass grafting?†. (18th July 2015) - Fawzy, Hosam; Elatafy, Elatafy; Elkassas, Marwan; Elsarawy, Emad; Morsy, Ahmed; Fawzy, Amr
Abstract : OBJECTIVES: Atrial fibrillation (AF) is a common complication that increases the morbidity after open heart surgery. The pathophysiology is uncertain, and its prevention remains suboptimal. The aim of this study was to assess the efficiency of posterior pericardiotomy in decreasing the incidence of pericardial effusion and postoperative AF. METHODS: This multicentre randomized prospective study included 200 patients who underwent open heart surgery; coronary artery bypass grafting procedure between June 2010 and May 2012. A posterior pericardiotomy incision was done in Group I ( n = 100). A longitudinal incision, 4-cm long and 2-cm width, was made parallel and posterior to the left phrenic nerve, extending from the left inferior pulmonary vein to the diaphragm. Group II constituted the control group ( n = 100). Postoperative pericardial effusion was assessed by echocardiography and rhythm follow-up was monitored daily. RESULTS: The incidence of postoperative AF was significantly lower in the posterior pericardiotomy group than in the control group (13 vs 30%, P = 0.01). The number of patients with remarkable postoperative pericardial effusion was significantly lower in the posterior pericardiotomy group (15 vs 50 patients, P = 0.04). Tamponade developed in 3 patients in Group II ( P = 0.07). There was a significantly higher incidence of chest drainage in the posterior pericardiotomy group than in the control group (1041 ± 549 vs 911 ± 122 ml; P = 0.04). There was no significant difference between the two groups regarding hospital stay (8 vs 9 days, P > 0.05). CONCLUSIONS: Posterior pericardiotomy is a simple, safe and effective method for reducing the incidence of postoperative pericardial effusion and related atrial fibrillation by improving pericardial drainage after coronary artery bypass grafting.